Maternal synapsin autoantibodies are associated with neurodevelopmental delay - Bünger, Isabel; Makridis, Konstantin L.; Kreye, Jakob; Nikolaus, Marc; Sedlin, Eva; Ullrich, Tim; Hoffmann, Christian; Tromm, Johannes Vincent; Rasmussen, Helle Foverskov; Milovanovic, Dragomir; Höltje, Markus; Prüss, Harald; et al. (Frontiers in Immunology, 2023)
Maternal autoantibodies can be transmitted diaplacentally, with potentially deleterious effects on neurodevelopment. Synapsin 1 (SYN1) is a neuronal protein that is important for synaptic communication and neuronal plasticity. While monoallelic loss of function (LoF) variants in the SYN1 gene result in X-linked intellectual disability (ID), learning disabilities, epilepsy, behavioral problems, and macrocephaly, the effect of SYN1 autoantibodies on neurodevelopment remains unclear. We recruited a clinical cohort of 208 mothers and their children with neurologic abnormalities and analyzed the role of maternal SYN1 autoantibodies. We identified seropositivity in 9.6% of mothers, and seropositivity was associated with an increased risk for ID and behavioral problems. Furthermore, children more frequently had epilepsy, macrocephaly, and developmental delay, in line with the SYN1 LoF phenotype. Whether SYN1 autoantibodies have a direct pathogenic effect on neurodevelopment or serve as biomarkers requires functional experiments.